1784-PUB: Empagliflozin (EMPA) Enhances Vascular Insulin Sensitivity and Lowers Plasma ICAM in Subjects with Type 2 Diabetes (T2D) - NGUYEN, THI; JAHN, LINDA; HARTLINE, LEE; AYLOR, KEVIN W.; BARRETT, EUGENE (Diabetes (New York, N.Y.), 2023)
Background: The mechanism(s) by which sodium-glucose cotransporter 2 inhibitor (SGLT2i) use improves cardiovascular and renal outcomes in T2D are not well-defined. We hypothesized that EMPA would increase vascular insulin sensitivity and decrease endothelial cell (EC) stress markers in T2D. Study Design: Ten 18-60 years-old persons with T2D, 6.5 < a1c 3 months, were studied. we measured vascular stiffness (pulse wave separation analysis), ec function (flow-mediated dilation (fmd)), and stress biomarkers (elisa) before after a 2-hour, 1 mu min kg euglycemic clamp at 0 12 weeks treatment with 10 mg empa daily. results: not wk 0, but wks, insulin decreased forward backward arterial pressures from 28±3 to 20±2 24±3 13±1 mmhg, respectively, (p<0.02, each) improved the fmd response (p="0.02)," indicating function. peripheral systolic diastolic unchanged by week declined (p<0.03, treatment. lowered baseline post-insulin plasma icam-1 (p<0.002, increased vcam-1 (p<0.0005). infusion pecam-1 (p<0.03) vasoconstrictor endothelin-1 (p<0.01) comparably or without e-selectin s100a8 9 did change significantly either empa. decrease suggests that inflammation. insulin’s action lower appeared independent of empa, may contribute empa’s beneficial actions. Interpretation: EMPA for 12 weeks enhanced insulin’s action to: 1) diminish arterial stiffness, 2) enhance EC function including biomarker release, and 3) lower blood pressure. Improved vascular insulin sensitivity may contribute to the improved CVD outcomes seen with SGLTi treatment.